Laser double optical resonance excitation-ionization of Mo with optogalvanic detection. (17th January 2022) - Lu, Hu; Varvarezos, Lazaros; Nicolosi, Piergiorgio; Andrighetto, Alberto; Scarpa, Daniele; Mariotti, Emilio; Costello, John T
Abstract: We report on the first measurement of resonant three-step, two-colour ionization of atomic molybdenum, using a hollow cathode lamp (HCL) with optogalvanic detection. Wavelength scans were made for two specific transitions involved in the ionization pathways under investigation, namely 4d 5 ( 6 S)5s 7 S3 –4d 5 ( 6 S)5p 7 P4 and 4d 5 ( 6 S)5p 7 P4 –4d 5 ( 6 S)6d 7 D5 . So-called 'slow' and 'fast' optogalvanic signals were respectively observed for each resonant quantum jump and for the simultaneous excitation of the two laser frequencies. This successful detection confirms the HCL as a cost effective spectroscopic investigation tool. In particular its use in the optogalvanic mode of operation allows one to precisely, easily and reliably tune the wavelength of one or more lasers to resonances of interest for experiments in the general domain of atomic vapour laser isotope selection (AVLIS). This activity has been undertaken in the framework of the Selective Production of Exotic Species (SPES) project at the ISOL facility of the Legnaro National Laboratories of INFN. These measurements are a necessary step towards the realization of the MOLAS subproject of SPES, whose aim is to verify the production of 99m technetium for medical application via laser ionization of the 99 uma isotope of Molibdenum.